Penguatan Pendidikan Karakter Tanggung Jawab melalui Pembelajaran Pendidikan Agama Islam Di SMPN 1 Pacet - Nurjanna Nurjanna; Mohammad Maulana Nur Kholis (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research uses a qualitative research method with a case study approach. Data collection techniques using observation, interview and documentation. Data sources in this study include principals, Islamic Religious Education teachers and students. Data analysis techniques used in this study are data collection, data reduction, data presentation, conclusion drawing. Triangulation used to test the validity of data triangulation techniques and sources. Research Results: (1) The method of strengthening responsibility character education through Islamic religious education learning is by habituation, exemplary, and advice carried out by students to carry out their duties and responsibilities as a Muslim-muslimah: (2) The implications of the method of strengthening responsibility character education through Islamic religious education learning The results of research findings in the field Attending school on time makes students more disciplined, throwing garbage in its place awareness that the need to keep the environment beautiful, clean and cleanliness is part of faith. Obeying worship through gemajusa learning makes students more accustomed to worship so that it becomes a habit that is always done and almsgiving is carried out by all students to make students care about others through almsgiving.